BELAJAR MATEMATIKA MENYENANGKAN MELALUI APLIKASI MODEL MATH MAGIC - Asmaningtias, Yeni Tri (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
Math magic school is an institution courses that focus on math. Where students learn in a simple, easy, fast and precise. Math Magic special focus for the basic grade students (elementary to junior high) so that the method used more widely to the game. Before playing a game, Brain Gym is usually done in advance to assist students in learning mathematics, after the Brain Gym method is carried out such a game is a game of dominoes and a calculator paper.Keywords: Magic School Math, Brain Gym, Domino Card, Paper Calculator.